Significant electronic thermal transport in the conducting polymer poly(3,4-ethylenedioxythiophene) - Weathers, Annie (Advanced materials (Deerfield Beach, Fla.), 2015)
© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.